2010
DOI: 10.1007/s00203-010-0654-9
|View full text |Cite
|
Sign up to set email alerts
|

Paenibacillus polymyxa JB05-01-1 and its perspectives for food conservation and medical applications

Abstract: The aim of this study was to isolate a novel bacterial strain with strong and broad spectrum antibacterial activity from a livestock feed prebiotic supplement. A novel strain, termed Paenibacillus polymyxa JB05-01-1, was isolated using traditional microbiological methods and identified on the basis of its phenotypic and biochemical properties as well as its 16S rRNA gene sequence. This strain was able to inhibit growth of gram-negative bacteria including Escherichia coli RR1, Pseudomonas fluorescens R73, Panto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Application of this culture-dependent assay to screen for Paenibacillus spp. in nondairy environments could facilitate identification of strains with important metabolic capabilities (e.g., production of polymyxin, bioremediation, or nitrogen-fixing ability) of importance to agriculture, food processing, and medicine (29,37,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of this culture-dependent assay to screen for Paenibacillus spp. in nondairy environments could facilitate identification of strains with important metabolic capabilities (e.g., production of polymyxin, bioremediation, or nitrogen-fixing ability) of importance to agriculture, food processing, and medicine (29,37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our assay has potential for use as a screening tool to isolate novel enzyme-producing Paenibacillus spp. from other foods (31) and the natural environment (37), as previous identification of Paenibacillus strains has led to the discovery of many compounds with promising applications in agriculture and medicine (29).…”
mentioning
confidence: 99%
“…They grow at chilled temperatures of Ͻ10°C (21,30), which explains why they appear frequently in harvested vegetables and grains (19), chilled foods (8,21,23,31), natural wood, as well as humus (18,34). Secondary metabolites of paenibacilli have been investigated for antimicrobial properties with the aim to improve the microbiological safety of foods with extended shelf lives (22,26,47,64,66,67). On the other hand, Paenibacillus larvae is known to cause infectious disease in bees (3,9), and Paenibacillus species in cultures of chilled human blood with potential pathogenicity toward humans have been reported (50,56).…”
mentioning
confidence: 99%
“…The production of natural EPS like those produced by P. polymyxa SQR-21 provides an opportunity to replace synthetic (ESP) compounds that are mixtures of monosaccharides and glucuronic acid (Raza et al 2011). The P. polymyxa JB05-01-1 isolated from a livestock probiotic feed supplement has strong inhibitory activity against Gram-negative bacteria including E. coli RR1, P. Xuorescens R73, Pantoea agglomerans BC1, Butyrivibrio Wbrisolvens OR85, and Fibrobacter succinogenes (Naghmouchi et al 2011). This anti-Gram-negative activity is ascribed to the production of colistin A/B.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent report, we showed that the inhibitory substances produced by P. polymyxa JB05-01-1 have similar physicochemical properties (temperature, pH, and solvents resistance) to that of polymyxins. (Naghmouchi et al 2011). …”
Section: Spectrum Of Activitymentioning
confidence: 93%